Case Study First Aid in Art Therapy and its liberating role in Bosnia and Herzegovina Temporary Reception Centers for Migrants and Refugees - Lousa, Teresa V.; Hughet, Malena (Arte, Individuo y Sociedad, 2022)
First Aid in Art Therapy is a therapeutic approach carried out in Bosnian migrants and refugee camps from October 2019 to the present.. In an extremely challenging context for therapists and beneficiaries, Art Therapy sessions were held according to the methodology of free creative expression, with a high degree of adjustability. A non-directed work prioritizing each participant’s needs, spontaneity, and the factor of transitoriness, either of conditions or of emotions, was revealed to be the appropriate approach within a context of humanitarian crisis. In this study, the theoretical foundations of Carl Jung and Nise da Silveira[1] were used, especially with regard to the concept of Archetype, which is essential for a better understanding of the images produced in these sessions. It could be observed in the migrants and refugees’ work that certain repeated patterns appeared, for example: feminine figures and mandalas: which coincide with two strong archetypes that will be highlighted.